Iodine nutrition and its assessment during pregnancy: a need for concern - Bharathi, M. Naga; Kumar, K. Eswar; Prasad, K.; Srinivas, Y. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Micro nutrient iodine was essential in biosynthesis of thyroid hormones (TH). These hormones play a vital role in the growth and development of human beings at various stages of life. TH are required for normal brain development at embryonic, fetal and at past natal stages. If deficiency of iodine occurs then thyroid hormone production was impaired, if deficiency of TH occurs it can cause irreversible damage of brain which leads to various disorders like metal retarded ness, cretinism and goiter known as iodine deficiency disorders (IDD). When compared to normal adults, pregnant women and school children 5-12 years age are more vulnerable IDD. Due to the physiological variations during pregnancy iodine requirements rose significantly from 150 µg/day in non-pregnant adult women to 250 μg/day. However recent iodine nutrition studies showed adequate iodine status but few countries like Sweden and South Africa showed iodine deficiency. This review gives an over view on iodine nutrition on global front.